Design of electronic control device and control algorithm for rice transplanter - Lian, H; Xiwen, L; Zuoxi, Z; Zhigang, Z; Junwan, H; Bin, C (Nong ye gong cheng xue bao, 2009)
To study agricultural machine navigation and variable operation, the steering, transmission and transplanting control system of a Kubota rice transplanter were modified from manual control system to electronic control system using DC motors. A dynamic dead zone control algorithm was designed with varied dead zones for different movement direction to increase the stability of the dynamic position closed loop control. The tracing experiment results showed that the dynamic responsive performance of the modified steering control system was good. The field experiment results indicated that the rice transplanter controlled by the electronic control system worked as well as driven by a human driver in paddy field.